Substituição parcial do milho por fontes energéticas para bovinos de corte em pastejo - Cardoso, Adriano Borges (2013)
The present dissertation was elaborated based on two experiments with beef cattle supplemented under grazing conditions in Brachiaria brizantha cv. Marandu during the rainy season. The first experiment objective was to evaluate the partial replacement of corn grain (50%) by alternative energetic sources in concentrate supplement consumption, digestibility, ruminal protein bio-synthesis, microbial efficiency, ruminal N-NH3 and ruminal liquid pH. There were used five Nelore beef cattle whit an initial weight of 367.8 Kg in a 5x5 Latin square experimental design with five supplementation treatments: mineral supplementation; corn grain + soybean meal + urea; corn grain + millet grain + soybean meal + urea; corn grain + soybean hulls + soybean meal + urea; corn grain + sorghum grain + soybean meal + urea. The supplements were balanced to have 30% of crude protein (CP), offering 1 Kg/animal/day. It was observed a reduction in forage dry matter intake (DMI) for all supplemented animals caused by a substitution effect (mean of 0,98 g DM of forrage/g DM of supplement). Total digestible nutrients (TDN) were not affected by treatments (P>0.05), but it was observed an increase of CP and NFC intake (P<0.05) in the supplemented treatments. There were no significant differences (P>0.05) in N-NH3 ruminal liquid before supplementation (0:00 hours), however there was a supplementation effect on this variable four hours after the supplements were furnished. Microbial efficiency and ruminal microbial crude protein synthesis where no affected (P>0.05) by treatments, there were no verified effects (P>0.05) on ruminal pH. Regardless of the energetic fount, the energetic-proteic supplement offered to the beef cattle during the rainy season grazing Brachiaria brizantha cv. Marandu whit a potentially digestible dairy dry matter allowance of 4.50 Kg DM/100 kg LW/Day, caused a substitutive effect, reducing grass dry matter intake. The second experiment objective was to evaluate the partial substitution of corn grain (50%) with alternative energetic supplements on weight gain and economic results in beef cattle grazing Brachiaria brizantha cv. Manrandu during the rainy season. There were used 20 Nelore 12 beef cattle with a mean initial weight of 306.25 Kg. The experimental design was completely randomized with four treatments and five replicates. Treatments were: mineral supplementation; corn grain + soybean meal + urea; corn grain + millet grain + soybean meal + urea; corn grain + soybean hulls + soybean meal + urea; corn grain + sorghum grain + soybean meal + urea. The supplements were balanced to have 30% of crude protein (CP), offering 1 Kg/animal/day. There were no effects on average dairy gain, final weight, and total weight gain by the treatments. Economic results on this experiment indicate the absence of benefits by concentrate supplementation. The lack of an increase of weight gain with a higher economic cost per animal for the treatments receiving concentrate supplementation reflected in a diminishing benefit/cost result. Concentrate supplementation in beef cattle during the rainy season grazing Brachiaria brizantha cv. Marandu a potentially digestible dairy dry matter allowance of 4.82 Kg DM/100kg LW/day did not affect animal dairy weight gain. Since the absence of increasing weight gain, the supplementation under grazing condition did not present an economical advantage to be recommended.